The utilisation of instagram @dinkeskota.bdg in the dissemination of information regarding health services for the community: A virtual ethnographic study on the content analysis of health service reels on the account @dinkeskota.bdg in Bandung - Prasanti, Ditha; Fuady, Ikhsan (Bulan Sabit Merah Indonesia, 2024)
This research focuses on the utilisation of the Instagram account @dinkeskota.bdg for the dissemination of health service information to the community in Bandung. In this digital era, social media, particularly Instagram, has become an increasingly important platform for providing health information swiftly and engagingly. The study employs a virtual ethnographic approach to explore the interactions established between the account managers and followers through the reels content published over the past six months. The objectives of this research are to (1) ascertain the interactions occurring within the reels content concerning the health services provided by the Bandung City Health Office; and (2) identify the verbal and non-verbal language employed by followers in their responses to the reels content. The analysis focuses on the reels content, particularly the comments and reactions left by users. The findings indicate that there is significant interaction among followers regarding the uploaded content. The analysis of the reels content, specifically concerning the language used in the comments, suggests that followers express positive and supportive verbal expressions, while also employing emojis and symbols as forms of non-verbal expression. This research concludes with two key points: (1) the existence of interactions among followers of @dinkeskota.bdg; and (2) the presence of verbal language manifested in follower responses and non-verbal language represented by symbols such as likes or loves on the viewed reels content. Although the interaction in the form of comments from viewers remains limited, this presents an opportunity for the Bandung City Health Office to continue innovating in content development and to leverage various new features on Instagram. Furthermore, collaboration with health influencers could serve as a beneficial strategy to reach a broader audience.